Responding to innovative challengers in finance - pathways for success - Coutinho, João Maria Jardim De Castro Pereira (2023)
The dynamic landscape of the finance industry is witnessing a notable rise in the emergence of innovative challengers, disrupting incumbents and their practices. This study explores incumbents´ pathways for success in responding to these innovative challengers by developing a theoretical framework, from literature, to then discuss the specific challenges in consumer finance, using BNP Paribas as a case study. The model identifies and analyses four strategies that have allowed incumbents to survive and prosper; (1) organizational learning; (2) leveraging the network; (3) adapting internal operations; (4) autonomy and organizational culture.